2022
DOI: 10.1177/17085381221093855
|View full text |Cite
|
Sign up to set email alerts
|

Five-year survival after retroperitoneal oncologic resection with and without vascular surgeon intervention

Abstract: Objectives Retroperitoneal tumor resection commonly disturbs major vessels; therefore, surgical teams can recruit vascular surgeons to prevent injuries and improve the prognosis of oncologic patients. The objective of the present study is to establish long-term survival after retroperitoneal tumor resection surgery with an emphasis on the potential impact of preventing or repairing major vessel injuries when tumors are adjacent to the aorta or vena cava. Methods Retrospective case series including all cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…12 Importance of planned assistance of vascular surgeons was emphasized in another recent study with a positive impact on outcomes. 13 The objective of our study at this time was to update and re-evaluate the outcomes of vascular reconstructions in extremity STS based on a large group of patients from 2 tertiary centers. This study showed a high limb salvage rate of 89.4% at 24 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…12 Importance of planned assistance of vascular surgeons was emphasized in another recent study with a positive impact on outcomes. 13 The objective of our study at this time was to update and re-evaluate the outcomes of vascular reconstructions in extremity STS based on a large group of patients from 2 tertiary centers. This study showed a high limb salvage rate of 89.4% at 24 months after surgery.…”
Section: Discussionmentioning
confidence: 99%